Sevoflurane Exacerbates Cognitive Impairment Induced by Aβ1–40 in Rats through Initiating Neurotoxicity, Neuroinflammation, and Neuronal Apoptosis in Rat Hippocampus - Yue Tian; Ke-yan Chen; Li-dan Liu; Yun-xia Dong; Ping Zhao; Shan-bin Guo (Mediators of Inflammation)
Objective. This study was aimed at investigating whether sevoflurane inhalation induced cognitive impairment in rats with a possible mechanism involved in the event. Methods. Thirty-two rats were randomly divided into four groups of normal saline (NS) + O2, NS + sevoflurane (sevo), amyloid-β peptide (Aβ) + O2, and Aβ + sevo. The rats in the four groups received bilateral intrahippocampus injections of NS or Aβ. The treated hippocampus was harvested after inhaling 30% O2 or 2.5% sevoflurane. Evaluation of cognitive function was performed by Morris water maze (MWZ) and an Aβ1–42 level was determined by ELISA. Protein and mRNA expressions were executed by immunohistochemical (IHC) staining, Western blotting, and qRT-PCR. Results. Compared with the NS-treated group, sevoflurane only caused cognitive impairment and increased the level of Aβ1–42 of the brain in the Aβ-treated group. Sevoflurane inhalation but not O2 significantly increased glial fibrillary acidic protein (GFAP) and ionized calcium-binding adaptor molecule (IBA)1 expression in Aβ-treated hippocampus of rats. Expression levels for Bcl-xL, caspase-9, receptor for advanced glycation end products (RAGE) and brain-derived neurotrophic factor (BDNF) were significantly different in quantification of band intensity between the rats that inhaled O2 and sevoflurane in Aβ-treated groups (all P<0.05). Interleukin- (IL-) 1β, nuclear factor-κB (NF-κB), and inducible nitric oxide synthase (iNOS) mRNA expression increased after the rats inhaled sevoflurane in the Aβ-treated group (both P<0.01). There were no significant differences in the change of GFAP, IBA1, Bcl-xL, caspase-9, RAGE, BDNF, IL-1β, NF-κB, and iNOS in the NS + O2 and NS + sevo group (all P>0.05). Conclusion. Sevoflurane exacerbates cognitive impairment induced by Aβ1–40 in rats through initiating neurotoxicity, neuroinflammation, and neuronal apoptosis in rat hippocampus.